Firewalls don't stop dragons a step-by-step guide to computer security for non-techies - Parker, Carey (Apress, 2018)
Just how secure is your computer? Protecting your computer is like defending a medieval castle: moats and castle guards can be effective, but you'd bankrupt the kingdom trying to build something dragon-proof. Parker shows you dozens of no-brainer things we should all be doing to protect our computers and safeguard our data.